2022
DOI: 10.1080/00207543.2022.2044085
|View full text |Cite
|
Sign up to set email alerts
|

Platform-based product development in the process industry: a systematic literature review

Abstract: Platform-based product development has been applied extensively in discrete manufacturing industry to accommodate changing market demands. Nevertheless, while process industry manufacturers face similar market demands, the topic is only sparsely covered in literature. Through a systematic review of the literature, this study uncovers the definitions used, drivers behind, approaches and methods applied, and industry examples of platform-based product development in the process industry. Based on these analyses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 94 publications
0
44
0
Order By: Relevance
“…Furthermore, operational deficiencies as a threat to a firm's context confirm the past studies from the perspective of the extreme context. Past studies extensively demonstrated that operational deficiencies force firms to improve their innovation efforts to remain competitive (Lee et al, 2023;Nguyen et al, 2022;Afum et al, 2023;Andersen et al, 2023). This current study spots that firms are less prepared to realize the value of innovation attempts in the perception of extreme contexts without recognizing those deficiencies.…”
Section: Organizational Change Capacitymentioning
confidence: 73%
“…Furthermore, operational deficiencies as a threat to a firm's context confirm the past studies from the perspective of the extreme context. Past studies extensively demonstrated that operational deficiencies force firms to improve their innovation efforts to remain competitive (Lee et al, 2023;Nguyen et al, 2022;Afum et al, 2023;Andersen et al, 2023). This current study spots that firms are less prepared to realize the value of innovation attempts in the perception of extreme contexts without recognizing those deficiencies.…”
Section: Organizational Change Capacitymentioning
confidence: 73%
“…The definition of PFA stands as a pivotal undertaking in any industry's product development activity [47]. Given that this paper focuses on the modular architecture of products and collaborative decision-making design, the upper-level modular architecture is solely for configuring functional elements (choosing module instances) and aligning functional elements with physical components (determining the quantity of product variants and compound modules).…”
Section: Upper-level Optimizationmentioning
confidence: 99%
“…Different kind of design automation and design support systems are studied. The drivers behind platform-based approach in process industry manufacturing are cost reduction, productivity of product development and shorten lead time (Andersen et al, 2022). Design automatization (Willner et al, 2016a) and sales configurators are studied in ETO context.…”
Section: State Of the Artmentioning
confidence: 99%
“…Standardisation, modularisation, configuration, platforms, knowledge-based engineering, design automation, lean thinking are also used in project business. The drivers behind platform-based approach are cost reduction, productivity of product development and shorten lead time (Andersen et al, 2022). HVLV context is studied from engineering-to-order (ETO) and configurator viewpoints and from lean and supply management viewpoints.…”
Section: Introductionmentioning
confidence: 99%